1996
DOI: 10.1161/01.cir.93.10.1913
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Against Tissue Factor Shortens Tissue Plasminogen Activator Lysis Time and Prevents Reocclusion in a Rabbit Model of Carotid Artery Thrombosis

Abstract: TF exposure and activation of the extrinsic coagulation pathway play an important role in prolonging lysis time and mediating reocclusion after thrombolysis in this model. AP-1, a monoclonal antibody against TF, might be suitable as adjunctive therapy to TPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 29 publications
2
53
0
1
Order By: Relevance
“…37 Additionally, inhibition of TF activity may serve as adjunctive therapy to tissue plasminogen activator-induced thrombolysis by shortening the time needed for the lysis of thrombus and preventing reocclusion in the carotid rabbit model. 38 Our study demonstrates that TF pathway inhibition by local administration of TFPI or antibodies to TF is highly effective in reducing arterial thrombosis in human atherosclerotic lesions. In conclusion, our results clearly establish the causal role of TF activity in thrombus formation after atherosclerotic plaque disruption.…”
Section: Discussionmentioning
confidence: 64%
“…37 Additionally, inhibition of TF activity may serve as adjunctive therapy to tissue plasminogen activator-induced thrombolysis by shortening the time needed for the lysis of thrombus and preventing reocclusion in the carotid rabbit model. 38 Our study demonstrates that TF pathway inhibition by local administration of TFPI or antibodies to TF is highly effective in reducing arterial thrombosis in human atherosclerotic lesions. In conclusion, our results clearly establish the causal role of TF activity in thrombus formation after atherosclerotic plaque disruption.…”
Section: Discussionmentioning
confidence: 64%
“…22 Because of the dual function of TFPI as a direct inhibitor of factor Xa and as an inhibitor of the catalytic tissue factor/VIIa complex, we are unable to distinguish between the relative role of factor Xa and tissue factor/factor VIIa as a target of TFPI gene therapy. Nonetheless, studies of specific factor Xa inhibitors 23 and tissue factor-blocking antibodies 24 have demonstrated that both factor Xa and tissue factor play essential roles in arterial thrombogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Finally, previous studies from our own group have demonstrated that inhibition of formation of TF/FVII complex results in marked antithrombotic effects. [7][8][9] TFPI is a Kunitz-type serine protease inhibitor of Ϸ34 kDa. 11 TFPI is a potent inhibitor of the factor VIIa/TF complex in the presence of factor Xa and is also a direct inhibitor of factor Xa.…”
Section: Discussionmentioning
confidence: 99%